Einfluss von Steilaufstellung, Nachführung und Einsatz bifazialer PV-Module auf den Speicherbedarf und die Kosten einer 100% EE-Versorgung Deutschlands - Krauter, Stefan; Khatibi, Arash (Tagungsband des 36. PV-Symposium, 18.-26 Mai 2021, online, ISBN 978-3-948176-14-3, S. 301-304.)

Comparison and Validation of Irradiance Data: Satellite Meteorological Dataset MERRA-2 vs. Meteonorm and German Weather Service (DWD) - Khatibi, Arash; Krauter, Stefan (Proceedings of the 38th European Photovoltaic Solar Energy Conference and Exhibition (EUPVSEC 2021))
Access to precise meteorological data is crucial to be able to plan and install renewable energy systems such as solar power plants and wind farms. In case of solar energy, knowledge of local irradiance and air temperature values is very important. For this, various methods can be used such as installing local weather stations or using meteorological data from different organizations such as Meteonorm or official Deutscher Wetterdienst (DWD). An alternative is to use satellite reanalysis datasets provided by organizations like the National Aeronautics and Space Administration (NASA) and European Centre for Medium-Range Weather Forecasts (ECMWF). In this paper the “Modern-Era Retrospective analysis for Research and Applications” dataset version 2 (MERRA-2) will be presented, and its performance will be evaluated by comparing it to locally measured datasets provided by Meteonorm and DWD. The analysis shows very high correlation between MERRA-2 and local measurements (correlation coefficients of 0.99) for monthly global irradiance and air temperature values. The results prove the suitability of MERRA-2 data for applications requiring long historical data. Moreover, availability of MERRA-2 for the whole world with an acceptable resolution makes it a very valuable dataset.
Keywords: Energy potential estimation; Photovoltaic; Solar radiation; Temperature measurement; Satellite data; Meteonorm; MERRA-2; DWD

Validation and Performance of Satellite Meteorological Dataset MERRA-2 for Solar and Wind Applications - Khatibi, Arash; Krauter, Stefan (Energies)
Fast-growing energy demand of the world makes the researchers focus on finding new energy sources or optimizing already-developed approaches. For an efficient use of solar and wind energy in an energy system, correct design and sizing of a power system is of high importance and improving or optimizing the process of data obtaining for this purpose leads to higher performance and lower cost per unit of energy. It is essential to have the most precise possible estimation of solar and wind energy potential and other local weather parameters in order to fully feed the demand and avoid extra costs. There are various methods for obtaining local data, such as local measurements, official organizational data, satellite obtained, and reanalysis data. In this paper, the Modern-Era Retrospective analysis for Research and Applications dataset version 2 (MERRA-2) dataset provided by NASA is introduced and its performance is evaluated by comparison to various locally measured datasets offered by meteorological institutions such as Meteonorm and Deutscher Wetterdienst (DWD, or Germany’s National Meteorological Service) around the world. After comparison, correlation coefficients from 0.95 to 0.99 are observed for monthly global horizontal irradiance values. In the case of air temperature, correlation coefficients of 0.99 and for wind speed from 0.81 to 0.99 are observed. High correlation with ground measurements and relatively low errors are confirmed, especially for irradiance and temperature values, that makes MERRA-2 a valuable dataset, considering its world coverage and availability.
Keywords: Solar irradiance; MERRA 2; Meteonorm; DWD

Reduction of required storage capacities for a 100% renewable energy supply in Germany, if new PV systems are installed with east-west tracking systems at increased elevation angles - Krauter, Stefan; Rustemovic, D.; Khatibi, Arash (Proceedings of the 37th European Photovoltaic Solar Energy Conference, 07 - 11 September 2020)
Due to the strong reduction of PV prices, storage plays a dominating role in overall system costs. A steeper elevation angle would result in a more balanced seasonal PV yield, at the cost of PV yield reductions during summer, but allowing reduced storage capacities. Additionally, the effect of a single-axis tracking system has been investigated, generating more electricity during the morning and evening hours, thus reducing daily storage requirements. The necessary PV size and storage capacities required for the German energy supply (1,500 TWh after electrification of all sectors) via 100% renewable energies and a 50% solar share have been calculated via the HOMER Pro software, considering the bridging of periods of "dark lulls“ in winter, using costs of 2030 (Table 1). Results: The increase of module elevation angles above the typical 30° leads to a reduction of investment and supply costs. The optimum is reached at a cost reduction of -1.5% for an elevation angle at the latitude of the installation site. An explanation is that high elevation angles are favorable for clear winter days, but not at all for the critical days with diffuse irradiance only, so the battery capacity must be increased. For the same reason, tracking systems do not offer any cost advantage (at least for the ones without an option for horizontal positioning during diffuse days).
Keywords: Energy Storage; PV system integration; Large Grid-connected PV systems; Simulation; Energy Supply Options

Introduction of an Advanced Method for Testing of Battery Charge Controllers for Off-Grid PV Systems - Khatibi, Arash; Bendfeld, Jörg; Bermpohl, Wolfgang; Krauter, Stefan (Proceedings of the 33rd European Photovoltaic Solar Energy Conference, Amsterdam (Niederlande), 25.-29. Sept. 2017)

Testing and Analysis of Battery Charge Controllers for Off-Grid PV Systems - Khatibi, Arash; Bendfeld, Jörg; Bermpohl, Wolfgang; Krauter, Stefan (Proceedings of the 33rd European Photovoltaic Solar Energy Conference, Amsterdam (Niederlande), 25.-29. Sept. 2017)